Localization in periodic potentials : from Schrödinger operators to the Gross-Pitaevskii equation - Pelinovsky, Dmitry (London Mathematical Society lecture note series., 2011)
Describes modern methods in the analysis of reduced models of Bose-Einstein condensation in periodic lattices.